DEVELOPMENT OF ELECTROCHEMICAL BIOSENSOR BASED ON SCREEN-PRINTED CARBON ELECTRODES MODIFIED WITH MULTI-WALLED CARBON NANOTUBES/SILVER NANOPARTICLES NANOCOMPOSITE FOR URIC ACID DETECTION - Rahmatul Ula, Linta
Various biomolecules found in human body fluid can provide informations related to the body’s condition, thus can be utilized as biomarkers. One example is the monitoring of uric acid concentration, which has a relation with hyperuricemia. By developing point-of-care testing method to measure biomarkers’ concentration, the health monitoring process is expected to be easier, thus preventing worse scenarios from happening. Nonenzymatic electrochemical biosensor using screen-printed carbon electrode (SPCE) provide a practical and simple alternative for the implementation of point-of-care testing. By modifying the electrode’s surface using multi-walled carbon nanotubes/silver nanoparticles (MWCNT/AgNP) nanocomposite, the sensor’s detection performance can be increased, thus providing reliable detection results. In this research, MWCNT/AgNP nanocomposite was synthesized using oxidationreduction with reflux process, and was analyzed using SEM, TEM, EDS, FT-IR, Raman, and XRD characterization methods. The synthesized MWCNT/AgNP was drop-casted onto SPCE surface with optimization during the drop-casting process. The optimized MWCNT/AgNP-SPCE was used as uric acid electrochemical biosensor using differential pulse voltammetry (DPV) analysis method. Based on several testing, the obtained biosensor was selective and provided good uric acid detection with limit of detection (LOD), limit of quantification (LOQ), linear range, and linearity value of 76,4 nM, 254,7 nM, 10-1000 ?M, and 0,986 respectively. These performance values covered normal possible concentration of uric acid in serum, thus indicates that MWCNT/AgNP-SPCE had the potential to be used as uric acid electrochemical biosensor using serum sample.